Macao and U. S. -China Relations - Hao, Yufan; Wang, Jianwei (Lexington Books, 2010)
In this collection of essays, edited by Jianwei Wang and Yufan Hao, the contributor's explore the driving factors that lie behind Macau's increased visibility, including: the rapid economic development and growth, the 'one country, two system' administration under which they operate, the influx of foreign investment, and the role of Macau in China's foreign policy, especially as it relates to the United States. Macau underwent tremendous growth in various spheres during its evolution from a minor colonial power into a global player with increasing influence on the world stage. Their enhanced international profile is largely a result of their economic and political development over the 20th century, culminating with their handover to China in 1999. With more than 60 countries that have established consular services in Macau, and their membership in several international organizations — WTO, UNESDO, and the World Tourism Organization) — Macau continues to play an important role in the Eastern hemisphere. Macau's entrance into the world market improved their reputation in East Asia and led to spectacular economic growth, but it also attracted foreign investment, especially from the United States, that changed the cultural landscape. American influence has grown steadily in Macau, and with their increased exposure to international economics and politics, Macau's role as a buffer between China and United States is increasingly important. Macau and U.S.-Chinese Relations uses a local perspective to analyze the complicated relationship between these two world superpowers and Chinese foreign policy as a whole.